(untitled) (Journal of Comparative & International Higher Education, 2022)
Research has focused almost exclusively on ITA’s experiences as instructors, overlooking the ITA training class. This has led to the marginalization of Pre-Service ITA’s in the literature. The locus of potentially important learning, a descriptive, multiple case study examined the investment (Darvin & Norton, 2015) of 3 Pre-Service ITA’s in their ITA training class over one semester at a large U.S. university. Data included ITA’s weekly journals, individual interviews/ stimulated recalls, class assignments, and fieldnotes from classroom observations. Findings are presented as portraits of real, multifaceted ITA’s, then from cross-case analyses. Participants experienced the same course very differently, impacted most prominently by their ITA educators’ teaching approach, their exposure to teaching role models, and their home department structures. Recognizing the incredible diversity ITA’s represent, pedagogical implications suggest an “intense exposure experience” or teaching-training focused pedagogy be implemented -instead of test-centric pedagogies, situating ITA’s learning within un-simulated spaces with real undergraduates.